(untitled) (The Peerian Journal, 2022)
This article deals with the issues of documents and treaties of the WTO, in particular TRIPS. The two most important principles of the WTO legal system are the national regime and the convenience regime, which are called the principles of non-discrimination. These principles provide for the prohibition of discrimination between similar goods and services of different participating countries.